A yellowing-resistant transparent asphalt material and a method for preparing the same

CN122898150APending Publication Date: 2026-10-13GUANGDONG CHENGTAI INVESTMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611205252.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

受阻酚类抗氧剂虽可通过捕获自由基延缓热氧老化,但无法有效屏蔽紫外线对沥青分子链的光化学破坏;而常规紫外吸收剂如苯并三唑类虽具有一定光稳定作用,却易在高温加工或长期服役过程中迁移挥发,导致防护效果衰减

Benefits of technology

本发明通过将肉桂酸插层改性层状双金属氢氧化物与抗氧剂1010复配为复合抗氧剂,并与硬脂酸改性纳米二氧化钛协同引入沥青体系,形成紫外屏蔽-自由基捕获协同防护机制,实现透明沥青材料长期服役下的高耐黄变性能与稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786347279937-000001
    Figure REF-OBJ-1786347279937-000001
Patent Text Reader

Abstract

The application discloses a kind of yellowing-resistant transparent asphalt material and preparation method thereof, it is related to asphalt material technical field, to solve the technical problem of the insufficient yellowing resistance of transparent asphalt, its preparation method includes the following steps: step 1 uses cinnamic acid to carry out organic modification to layered double metal hydroxide, then mixed with antioxidant 1010, to obtain composite antioxidant;Step 2 heat shearing is carried out to hydrogenated styrene-butadiene block copolymer, then join light-colored hydrogenated rosin resin, water white low aromatic ring alkanes oil, styrene-butadiene rubber, ternary ethylene-propylene and stearic acid modified nano titanium dioxide, shear development, to obtain base asphalt;Step 3 under constant temperature, composite antioxidant is added to base asphalt and sheared, and heat preservation is carried out, to obtain yellowing-resistant transparent asphalt material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of asphalt materials technology, specifically to a yellowing-resistant transparent asphalt material and its preparation method. Background Technology

[0002] With the increasing demand for urban aesthetics and colored pavements, transparent asphalt materials have gradually become a research hotspot in the field of road engineering. However, traditional transparent asphalt, which uses light-colored resins and naphthenic oils to replace dark-colored matrix components, while giving the material translucency, also makes it face more severe aging challenges during service. The multiple coupling effects of light, oxygen, and heat not only lead to the accumulation of polar oxygen-containing functional groups such as carbonyl and sulfoxide groups in the asphalt components, triggering molecular chain oxidative breakage and rearrangement, but also macroscopically manifest as the material changing from colorless and transparent to yellowish-brown, i.e., the "yellowing" phenomenon. Yellowing not only seriously affects the aesthetics and landscape harmony of the pavement, but is also a direct manifestation of deep aging of asphalt - accompanied by the material becoming harder, more brittle, and less adhesive, ultimately leading to a significant shortening of the pavement's service life.

[0003] Current anti-aging modification technologies for transparent asphalt mainly focus on the addition of single antioxidants or the physical blending of UV absorbers. While hindered phenolic antioxidants can delay thermo-oxidative aging by capturing free radicals, they cannot effectively shield against the photochemical damage of UV rays to the asphalt molecular chains. Conventional UV absorbers, such as benzotriazoles, while possessing some photostable properties, are prone to migration and volatilization during high-temperature processing or long-term service, leading to a decrease in protective effectiveness. Layered bimetallic hydroxides (LDHs), due to their unique layered structure that reflects and absorbs UV rays, have been explored for asphalt anti-aging modification. However, inorganic LDHs have poor compatibility with the organic system of transparent asphalt, easily causing a decrease in transmittance and initiating phase separation due to differences in refractive index. Although nano-titanium dioxide has UV shielding capabilities, its strong hydrophilicity makes it difficult to disperse uniformly in a low-polarity transparent asphalt matrix, and excessive addition significantly reduces the material's transmittance. More importantly, none of the above-mentioned single modification methods can simultaneously solve the contradictory requirements of "maintaining initial light transmittance" and "inhibiting long-term yellowing" of transparent asphalt. It is urgent to achieve functional complementarity and performance balance through multi-component chemical synergy. Summary of the Invention

[0004] The present invention aims to provide a yellowing-resistant transparent asphalt material and its preparation method, so as to solve the related technical problems existing in the prior art.

[0005] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows: Step 1: Organically modify the layered bimetallic hydroxide with cinnamic acid, and then mix it with antioxidant 1010 to obtain a composite antioxidant; Step 2: The hydrogenated styrene-butadiene block copolymer is heated and sheared, and then light-colored hydrogenated rosin resin, water-white low-aromatic naphthenic oil, styrene-butadiene rubber, ethylene propylene diene monomer (EPDM) and stearic acid-modified nano-titanium dioxide are added. Shearing and development are carried out to obtain the base asphalt. Step 3: Add the composite antioxidant to the base asphalt under constant temperature, shear, and keep warm to obtain a transparent asphalt material resistant to yellowing.

[0006] More preferably, the components of the yellowing-resistant transparent asphalt material, by weight, are: 25-55 parts of light-colored hydrogenated rosin resin, 20-50 parts of water-white low-aromatic naphthenic oil, 6-15 parts of hydrogenated styrene-butadiene block copolymer, 3-6 parts of styrene-butadiene rubber, 2-5 parts of ethylene propylene diene monomer (EPDM), 0.2-0.4 parts of composite antioxidant, and 2-4 parts of stearic acid-modified nano-titanium dioxide.

[0007] More preferably, the preparation steps of the composite antioxidant are as follows: Layered bimetallic hydroxide was added to an ethanol-water mixture and stirred in a water bath to obtain a layered bimetallic hydroxide slurry. Cinnamic acid was added to the ethanol-water mixture to prepare a cinnamic acid solution. The cinnamic acid solution was mixed with the layered bimetallic hydroxide slurry, and the pH was adjusted to 3-4 with hydrochloric acid. The mixture was stirred in a water bath to obtain an organic layered bimetallic hydroxide suspension. The organic layered bimetallic hydroxide suspension was filtered, washed, dried, and ground to obtain an organic layered bimetallic hydroxide solid. The organic layered bimetallic hydroxide solid was mixed with antioxidant 1010 to obtain a composite antioxidant.

[0008] Preferably, the mass ratio of the layered bimetallic hydroxide to the ethanol-water mixed solvent is 1:10; the mass ratio of the cinnamic acid to the ethanol-water mixed solvent is 1:25; the ethanol-water mixed solvent is prepared by mixing ethanol and water at a volume ratio of 1:1; and the organic layered bimetallic hydroxide solid is mixed with antioxidant 1010 at a mass ratio of 3:1.2.

[0009] Preferably, the water bath temperature after mixing the layered bimetallic hydroxide and the ethanol-water mixed solvent is 60-65°C, and the stirring time is 1-1.5h; the water bath temperature after mixing the cinnamic acid solution and the layered bimetallic hydroxide slurry is 55-65°C, and the stirring time is 23-25h.

[0010] More preferably, the preparation steps of the stearic acid modified nano-titanium dioxide are as follows: Nano-titanium dioxide was dispersed in anhydrous ethanol and stirred for 10-15 min, then ultrasonically dispersed at 20-23℃ for 25-30 min to obtain a nano-titanium dioxide mixture. Stearic acid was added to the nano-titanium dioxide mixture, and after stirring for 10-15 min, it was ultrasonically dispersed at 35-40℃ for 25-30 min. Then, the temperature was raised to 65-70℃, and the mixture was magnetically stirred for 1.5-2 h. After centrifugation for 3-5 min, the resulting solution was allowed to stand at 20-25℃ for 11-13 h. The supernatant was discarded, and the lower solid-liquid mixture was dried at 75-85℃ for 1-1.5 h and ground to obtain stearic acid modified nano-titanium dioxide.

[0011] More preferably, the mass ratio of the nano-titanium dioxide, anhydrous ethanol and stearic acid is 1:20:0.2.

[0012] Preferably, in step 2, the heating shearing temperature is 145~155℃, the shearing speed is 5000~5500 r / min, and the shearing time is 1~2 h; the shearing development speed is 5000~5500 r / min, the shearing time is 50~60 min, the development temperature is 160~165℃, and the development time is 2~3 h.

[0013] More preferably, in step 3, the constant temperature is 160~165℃, the shearing speed is 5000~5500r / min, the shearing time is 45~55min, the heat preservation temperature is 160~170℃, and the heat preservation time is 40~50min.

[0014] Based on the above preparation method, the present invention also provides a yellowing-resistant transparent asphalt material.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention combines cinnamic acid-intercalated modified layered bimetallic hydroxide with antioxidant 1010 to form a composite antioxidant, and then introduces it into the asphalt system in synergy with stearic acid-modified nano-titanium dioxide to form a synergistic protection mechanism of ultraviolet shielding and free radical capture, thereby achieving high yellowing resistance and stability of transparent asphalt materials under long-term service.

[0016] A water-white low-aromatic naphthenic oil is used as the base oil phase to replace the dark aromatic components in conventional asphalt, ensuring the system's light transmittance. Light-colored hydrogenated rosin resin, through its rigid three-membered ring hydrogenated structure, improves the system's softening point and cohesiveness, compensating for the high-temperature performance loss caused by alkane oil. Together, they construct a transparent matrix framework. Hydrogenated styrene-butadiene block copolymer, with its saturated mesoblocks, provides the main elastic network and maintains transparency. The unsaturated double bonds of styrene-butadiene rubber impart low-temperature chain mobility to aid in resistance to low-temperature cracking, while ethylene propylene diene monomer (EPDM) rubber, with its fully saturated main chain structure, provides the system with long-term weather resistance. Cinnamic acid-intercalated organic layered bimetallic hydroxides introduce cinnamic acid anions into the interlayer via ion exchange, widening the interlayer spacing to enhance UV shielding effectiveness. Simultaneously, organic modification significantly improves the interfacial compatibility between the inorganic layers and the resin / polymer segments, preventing light transmittance attenuation caused by separation. Hindered phenolic antioxidant 1010 captures peroxide free radicals through a hydrogen atom transfer mechanism, blocking the thermo-oxidative aging chain reaction. Stearic acid-modified nano-titanium dioxide undergoes surface esterification, changing from hydrophilic to hydrophobic, ensuring uniform dispersion while retaining its ability to reflect and scatter solar radiation. Furthermore, hydrogen bonding between the hydroxyl groups of the layered bimetallic hydroxide layers and the residual Ti-OH groups on the surface of the stearic acid-modified nano-titanium dioxide further strengthens their interfacial bonding.

[0017] In this invention, the synergistic effect of ultraviolet shielding and free radical passivation effectively inhibits the formation of carbonyl groups and conjugated olefins, giving transparent asphalt materials continuous and stable resistance to yellowing. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the embodiments described are only some, not all, implementations of the present invention. Other implementations that can be obtained by those skilled in the art based on the embodiments of the present invention without creative effort all fall within the protection scope of the present invention.

[0019] It should be noted that the following quantities are by weight, with 1 part by weight equal to 1g; there are no special restrictions on the manufacturers of the raw materials involved in this invention, and they include, exemplarily, the following: light-colored hydrogenated rosin resin: model KE-604; water-white low-aromatic naphthenic oil: model KN4010, density 0.89g / cm³. 3 Hydrogenated styrene-butadiene block copolymer: Model G-1651, styrene content 33%; Styrene-butadiene rubber: density 0.91 g / cm³ 3Molecular weight 3000; EPDM: Molecular weight 30000; Layered bimetallic hydroxide: Magnesium aluminum carbonate type hydrotalcite, MgO 32.0~34.0%, Al2O3 19.9~21.9%; Nano titanium dioxide: Anatase type, particle size 20nm; Antioxidant 1010: Purity 98%; Anhydrous ethanol, cinnamic acid, hydrochloric acid and stearic acid are all analytical grade.

[0020] Example 1: A method for preparing a yellowing-resistant transparent asphalt material, comprising the following steps: Step 1: Take 10g of layered bimetallic hydroxide and add it to 100mL of a mixed solvent of ethanol and water in a volume ratio of 1:1. Transfer the solution to a three-necked flask and stir at high speed in a 60℃ water bath for 1h to obtain a layered bimetallic hydroxide slurry. Mix 4g of cinnamic acid with 100mL of a solvent of ethanol and water in a volume ratio of 1:1 to prepare a cinnamic acid solution. Mix the cinnamic acid solution with the layered bimetallic hydroxide slurry, adjust the pH to 3 with hydrochloric acid, and stir at high speed in a 55℃ water bath for 23h to obtain an organic layered bimetallic hydroxide suspension. Filter, wash, dry, and grind the organic layered bimetallic hydroxide suspension to obtain an organic layered bimetallic hydroxide solid. Mix the organic layered bimetallic hydroxide solid with antioxidant 1010 at a mass ratio of 3:1.2 to obtain a composite antioxidant. Step 2: Take 1g of nano-titanium dioxide and disperse it in 20mL of anhydrous ethanol. Stir for 10min and then sonicate at 20℃ for 25min to obtain a nano-titanium dioxide mixture. Add 0.2g of stearic acid to the nano-titanium dioxide mixture, stir for 10min, and then sonicate at 35℃ for 25min. Then raise the temperature to 65℃ and stir magnetically for 1.5h. After the reaction is complete, centrifuge for 3min using a high-speed centrifuge. Let the resulting solution stand at 20℃ for 11h to separate the layers. Discard the supernatant and dry the lower solid-liquid mixture in a 75℃ forced-air drying oven for 1h. Grind to obtain stearic acid modified nano-titanium dioxide. Step 3: By weight, heat 6 parts of hydrogenated styrene-butadiene block copolymer to 145°C and shear at a shear rate of 5000 r / min for 1 hour. Then add 25 parts of light-colored hydrogenated rosin resin, 20 parts of water-white low-aromatic naphthenic oil, 3 parts of styrene-butadiene rubber, 2 parts of ethylene propylene diene monomer (EPDM) and 2 parts of stearic acid-modified nano-titanium dioxide. Shear at a shear rate of 5000 r / min for 50 minutes and develop at 160°C for 2 hours to obtain the base asphalt. Step 4: At a constant temperature of 160℃, add 0.2 parts of composite antioxidant to the base asphalt and shear at a shearing speed of 5000r / min for 45min. After shearing, keep it at 160℃ for 40min to obtain yellowing-resistant transparent asphalt material.

[0021] Example 2: A method for preparing a yellowing-resistant transparent asphalt material, comprising the following steps: Step 1: Take 20g of layered bimetallic hydroxide and add it to 200mL of a mixed solvent of ethanol and water in a volume ratio of 1:1. Transfer the mixture to a three-necked flask and stir at high speed in a water bath at 63℃ for 1.3h to obtain a layered bimetallic hydroxide slurry. Mix 8g of cinnamic acid with 200mL of a solvent of ethanol and water in a volume ratio of 1:1 to prepare a cinnamic acid solution. Mix the cinnamic acid solution with the layered bimetallic hydroxide slurry, adjust the pH to 3.5 with hydrochloric acid, and stir at high speed in a water bath at 60℃ for 24h to obtain an organic layered bimetallic hydroxide suspension. Filter, wash, dry, and grind the organic layered bimetallic hydroxide suspension to obtain an organic layered bimetallic hydroxide solid. Mix the organic layered bimetallic hydroxide solid with antioxidant 1010 at a mass ratio of 3:1.2 to obtain a composite antioxidant. Step 2: Take 2g of nano-titanium dioxide and disperse it in 40mL of anhydrous ethanol. Stir for 13min and then sonicate at 22℃ for 27min to obtain a nano-titanium dioxide mixture. Add 0.4g of stearic acid to the nano-titanium dioxide mixture, stir for 13min, and then sonicate at 37℃ for 27min. Then raise the temperature to 67℃ and stir magnetically for 1.7h. After the reaction is complete, centrifuge for 4min using a high-speed centrifuge. Let the resulting solution stand at 23℃ for 12h to separate the layers. Discard the supernatant and place the lower solid-liquid mixture in an 80℃ drying oven to dry for 1.3h. Grind to obtain stearic acid modified nano-titanium dioxide. Step 3: By weight, heat 10 parts of hydrogenated styrene-butadiene block copolymer to 150℃ and shear at a shear rate of 5300 r / min for 1.5 h. Then add 40 parts of light-colored hydrogenated rosin resin, 35 parts of water-white low-aromatic naphthenic oil, 5 parts of styrene-butadiene rubber, 4 parts of ethylene propylene diene monomer (EPDM) and 3 parts of stearic acid-modified nano-titanium dioxide. Shear at a shear rate of 5300 r / min for 55 min and develop at 163℃ for 2.5 h to obtain the base asphalt. Step 4: At a constant temperature of 163℃, add 0.3 parts of composite antioxidant to the base asphalt and shear at a shearing speed of 5300r / min for 50min. After shearing, keep it at 165℃ for 45min to obtain yellowing-resistant transparent asphalt material.

[0022] Example 3: A method for preparing a yellowing-resistant transparent asphalt material, comprising the following steps: Step 1: Take 30g of layered bimetallic hydroxide and add it to 300mL of a mixed solvent of ethanol and water in a volume ratio of 1:1. Transfer the mixture to a three-necked flask and stir at high speed in a 65℃ water bath for 1.5h to obtain a layered bimetallic hydroxide slurry. Mix 12g of cinnamic acid with 300mL of a solvent of ethanol and water in a volume ratio of 1:1 to prepare a cinnamic acid solution. Mix the cinnamic acid solution with the layered bimetallic hydroxide slurry, adjust the pH to 4 with hydrochloric acid, and stir at high speed in a 65℃ water bath for 25h to obtain an organic layered bimetallic hydroxide suspension. Filter, wash, dry, and grind the organic layered bimetallic hydroxide suspension to obtain an organic layered bimetallic hydroxide solid. Mix the organic layered bimetallic hydroxide solid with antioxidant 1010 at a mass ratio of 3:1.2 to obtain a composite antioxidant. Step 2: Take 3g of nano-titanium dioxide and disperse it in 60mL of anhydrous ethanol. Stir for 15min and then sonicate at 23℃ for 30min to obtain a nano-titanium dioxide mixture. Add 0.6g of stearic acid to the nano-titanium dioxide mixture, stir for 15min, and then sonicate at 40℃ for 30min. Then raise the temperature to 70℃ and stir magnetically for 2h. After the reaction is complete, centrifuge for 5min using a high-speed centrifuge. Let the resulting solution stand at 25℃ for 13h to separate the layers. Discard the supernatant and place the lower solid-liquid mixture in an 85℃ drying oven for 1.5h. Grind to obtain stearic acid modified nano-titanium dioxide. Step 3: By weight, 15 parts of hydrogenated styrene-butadiene block copolymer were heated to 155°C and sheared at a shear rate of 5500 r / min for 2 hours. Then, 55 parts of light-colored hydrogenated rosin resin, 50 parts of water-white low-aromatic naphthenic oil, 6 parts of styrene-butadiene rubber, 5 parts of ethylene propylene diene monomer (EPDM) and 4 parts of stearic acid-modified nano-titanium dioxide were added and sheared at a shear rate of 5500 r / min for 60 minutes. The mixture was then developed at 165°C for 3 hours to obtain the base asphalt. Step 4: At a constant temperature of 165℃, add 0.4 parts of composite antioxidant to the base asphalt and shear at a shearing speed of 5500r / min for 55min. After shearing, keep warm at 170℃ for 50min to obtain yellowing-resistant transparent asphalt material.

[0023] Comparative Example 1: Compared with Example 3, unmodified nano-titanium dioxide was used, and the specific differences are as follows: Step 1: Take 30g of layered bimetallic hydroxide and add it to 300mL of a mixed solvent of ethanol and water in a volume ratio of 1:1. Transfer the mixture to a three-necked flask and stir at high speed in a 65℃ water bath for 1.5h to obtain a layered bimetallic hydroxide slurry. Mix 12g of cinnamic acid with 300mL of a solvent of ethanol and water in a volume ratio of 1:1 to prepare a cinnamic acid solution. Mix the cinnamic acid solution with the layered bimetallic hydroxide slurry, adjust the pH to 4 with hydrochloric acid, and stir at high speed in a 65℃ water bath for 25h to obtain an organic layered bimetallic hydroxide suspension. Filter, wash, dry, and grind the organic layered bimetallic hydroxide suspension to obtain an organic layered bimetallic hydroxide solid. Mix the organic layered bimetallic hydroxide solid with antioxidant 1010 at a mass ratio of 3:1.2 to obtain a composite antioxidant. Step 2: By weight, 15 parts of hydrogenated styrene-butadiene block copolymer were heated to 155°C and sheared at a shear rate of 5500 r / min for 2 hours. Then, 55 parts of light-colored hydrogenated rosin resin, 50 parts of water-white low-aromatic naphthenic oil, 6 parts of styrene-butadiene rubber, 5 parts of ethylene propylene diene monomer (EPDM) and 4 parts of nano-titanium dioxide were added and sheared at a shear rate of 5500 r / min for 60 minutes. The mixture was then developed at 165°C for 3 hours to obtain the base asphalt. Step 3: At a constant temperature of 165℃, add 0.4 parts of composite antioxidant to the base asphalt and shear at a shearing speed of 5500r / min for 55min. After shearing, keep warm at 170℃ for 50min to obtain yellowing-resistant transparent asphalt material.

[0024] Comparative Example 2: Compared with Example 3, the layered bimetallic hydroxide used was not modified. The specific differences are as follows: Step 1: Mix layered bimetallic hydroxide and antioxidant 1010 at a mass ratio of 3:1.2 to obtain a composite antioxidant; Step 2: Take 3g of nano-titanium dioxide and disperse it in 60mL of anhydrous ethanol. Stir for 15min and then sonicate at 23℃ for 30min to obtain a nano-titanium dioxide mixture. Add 0.6g of stearic acid to the nano-titanium dioxide mixture, stir for 15min, and then sonicate at 40℃ for 30min. Then raise the temperature to 70℃ and stir magnetically for 2h. After the reaction is complete, centrifuge for 5min using a high-speed centrifuge. Let the resulting solution stand at 25℃ for 13h to separate the layers. Discard the supernatant and place the lower solid-liquid mixture in an 85℃ drying oven for 1.5h. Grind to obtain stearic acid modified nano-titanium dioxide. Step 3: By weight, 15 parts of hydrogenated styrene-butadiene block copolymer were heated to 155°C and sheared at a shear rate of 5500 r / min for 2 hours. Then, 55 parts of light-colored hydrogenated rosin resin, 50 parts of water-white low-aromatic naphthenic oil, 6 parts of styrene-butadiene rubber, 5 parts of ethylene propylene diene monomer (EPDM) and 4 parts of stearic acid-modified nano-titanium dioxide were added and sheared at a shear rate of 5500 r / min for 60 minutes. The mixture was then developed at 165°C for 3 hours to obtain the base asphalt. Step 4: At a constant temperature of 165℃, add 0.4 parts of composite antioxidant to the base asphalt and shear at a shearing speed of 5500r / min for 55min. After shearing, keep warm at 170℃ for 50min to obtain yellowing-resistant transparent asphalt material.

[0025] Comparative Example 3: Compared with Example 3, antioxidant 1010 was used to replace the compound antioxidant. The specific differences are as follows: Step 1: Take 3g of nano-titanium dioxide and disperse it in 60mL of anhydrous ethanol. Stir for 15min and then sonicate at 23℃ for 30min to obtain a nano-titanium dioxide mixture. Add 0.6g of stearic acid to the nano-titanium dioxide mixture, stir for 15min, and then sonicate at 40℃ for 30min. Then raise the temperature to 70℃ and stir magnetically for 2h. After the reaction is complete, centrifuge for 5min using a high-speed centrifuge. Let the resulting solution stand at 25℃ for 13h to separate the layers. Discard the supernatant and place the lower solid-liquid mixture in an 85℃ drying oven for 1.5h. Grind to obtain stearic acid modified nano-titanium dioxide. Step 2: By weight, 15 parts of hydrogenated styrene-butadiene block copolymer were heated to 155°C and sheared at a shear rate of 5500 r / min for 2 hours. Then, 55 parts of light-colored hydrogenated rosin resin, 50 parts of water-white low-aromatic naphthenic oil, 6 parts of styrene-butadiene rubber, 5 parts of ethylene propylene diene monomer (EPDM) and 4 parts of stearic acid-modified nano-titanium dioxide were added and sheared at a shear rate of 5500 r / min for 60 minutes. The mixture was then developed at 165°C for 3 hours to obtain the base asphalt. Step 3: At a constant temperature of 165℃, add 0.4 parts of antioxidant 1010 to the base asphalt and shear at a shearing speed of 5500r / min for 55min. After shearing, keep warm at 170℃ for 50min to obtain yellowing-resistant transparent asphalt material.

[0026] Performance testing: The asphalt materials of Examples 1-3 and Comparative Examples 1-3 were prepared into samples for testing; Marshall stability test: Refer to the method in JTG 3410-2025 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the sample size is φ101.6mm×63.5mm, the loading rate of the tester is 50.8mm / min, and the test temperature is 60℃; UV aging test: The sample was placed in a UV radiation test chamber with UV-B type UV light and a radiation intensity of 141 W / m². 2 The temperature range is 60℃, the radiation time is 144h, and then the Marshall stability test is performed after it is taken out. Yellowing test: Using a UVA-340m ultraviolet lamp with a radiation intensity of 60W / m 2 The yellowing index ΔYi was measured using a spectrophotometer after 360 hours at a temperature of 180℃. The yellowing index is classified into the following levels: Level 0 indicates no discoloration, with ΔYi not exceeding 1.5; Level 1 indicates very slight discoloration, with ΔYi between 1.6 and 3.0; Level 2 indicates slight discoloration, with ΔYi between 3.1 and 6.0; Level 3 indicates significant discoloration, with ΔYi between 6.1 and 9.0; Level 4 indicates substantial discoloration, with ΔYi between 9.1 and 12.0; Level 5 indicates severe discoloration, with ΔYi greater than 12.0. All test results are shown in Table 1.

[0027] Table 1

[0028] According to the data in Table 1, the yellowing-resistant transparent asphalt materials prepared in Examples 1-3 of this invention maintained a high level of Marshall stability and a yellowing grade of 0 after accelerated UV aging, indicating that they possess excellent thermo-oxidative and UV-induced synergistic anti-aging capabilities and color stability. Comparative Example 1, due to the use of unmodified nano-titanium dioxide, resulted in uneven dispersion of inorganic particles in the asphalt matrix, leading to interface defects. After aging, the stability decreased significantly, and the yellowing grade increased to level 2. Comparative Example 2, due to the lack of organic intercalation modification of the layered bimetallic hydroxide, had poor compatibility between the layers and the organic phase of the asphalt. This limited the UV shielding effect and triggered phase separation, further deteriorating the stability after aging and reaching a yellowing grade of level 3. Comparative Example 3, by only adding hindered phenolic antioxidant 1010 without compounding with organically modified layered bimetallic hydroxide, could not effectively suppress the photochemical breakage of molecular chains induced by UV light due to the single free radical capture mechanism. After aging, the stability decreased most significantly, and the yellowing grade reached level 4. The above comparison shows that no single modification method can simultaneously meet the requirements of UV resistance and thermo-oxidative aging resistance. The progressive performance degradation trend of Comparative Examples 1 to 3 confirms the necessity of the synergistic introduction of organic modified layered bimetallic hydroxide and stearic acid modified nano-titanium dioxide. This makes the stability decay of the examples under long-term UV irradiation significantly lower than that of the comparative examples, and the yellowing level is the best level 0. This fully verifies the significant advantages of the multi-component chemical synergistic strategy of the present invention in suppressing the formation of carbonyl and conjugated olefins in transparent asphalt and maintaining long-term color stability.

[0029] It will be apparent to those skilled in the art that the present invention is not limited to the specific details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and core features of the invention. Therefore, the above embodiments should be considered exemplary rather than restrictive in any respect. The scope of protection of the present invention is defined by the appended claims, not by the foregoing description, and is therefore intended to encompass all variations in the meaning and scope of the equivalents of the claims within the scope of the present invention.

Claims

1. A method for preparing a yellowing-resistant transparent asphalt material, characterized in that: Includes the following steps: Step 1: Organically modify the layered bimetallic hydroxide with cinnamic acid, and then mix it with antioxidant 1010 to obtain a composite antioxidant; Step 2: The hydrogenated styrene-butadiene block copolymer is heated and sheared, and then light-colored hydrogenated rosin resin, water-white low-aromatic naphthenic oil, styrene-butadiene rubber, ethylene propylene diene monomer (EPDM) and stearic acid-modified nano-titanium dioxide are added. Shearing and development are carried out to obtain the base asphalt. Step 3: Add the composite antioxidant to the base asphalt under constant temperature, shear, and keep warm to obtain a transparent asphalt material resistant to yellowing.

2. The method for preparing a yellowing-resistant transparent asphalt material according to claim 1, characterized in that: The components of the yellowing-resistant transparent asphalt material, by weight, are: 25-55 parts of light-colored hydrogenated rosin resin, 20-50 parts of water-white low-aromatic cycloalkane oil, 6-15 parts of hydrogenated styrene-butadiene block copolymer, 3-6 parts of styrene-butadiene rubber, 2-5 parts of ethylene propylene diene monomer (EPDM), 0.2-0.4 parts of composite antioxidant, and 2-4 parts of stearic acid-modified nano-titanium dioxide.

3. The method for preparing a yellowing-resistant transparent asphalt material according to claim 1, characterized in that: The preparation steps of the composite antioxidant are as follows: Layered bimetallic hydroxide was added to an ethanol-water mixture and stirred in a water bath to obtain a layered bimetallic hydroxide slurry. Cinnamic acid was added to the ethanol-water mixture to prepare a cinnamic acid solution. The cinnamic acid solution was mixed with the layered bimetallic hydroxide slurry, and the pH was adjusted to 3-4 with hydrochloric acid. The mixture was stirred in a water bath to obtain an organic layered bimetallic hydroxide suspension. The organic layered bimetallic hydroxide suspension was filtered, washed, dried, and ground to obtain an organic layered bimetallic hydroxide solid. The organic layered bimetallic hydroxide solid was mixed with antioxidant 1010 to obtain a composite antioxidant.

4. The method for preparing a yellowing-resistant transparent asphalt material according to claim 3, characterized in that: The mass ratio of the layered bimetallic hydroxide to the ethanol-water mixed solvent is 1:10; the mass ratio of the cinnamic acid to the ethanol-water mixed solvent is 1:25; the ethanol-water mixed solvent is prepared by mixing ethanol and water at a volume ratio of 1:1; the organic layered bimetallic hydroxide solid is mixed with antioxidant 1010 at a mass ratio of 3:1.

2.

5. The method for preparing a yellowing-resistant transparent asphalt material according to claim 3, characterized in that: The water bath temperature after mixing the layered bimetallic hydroxide and the ethanol-water mixed solvent is 60-65℃, and the stirring time is 1-1.5h; the water bath temperature after mixing the cinnamic acid solution and the layered bimetallic hydroxide slurry is 55-65℃, and the stirring time is 23-25h.

6. The method for preparing a yellowing-resistant transparent asphalt material according to claim 1, characterized in that: The preparation steps of the stearic acid modified nano-titanium dioxide are as follows: Nano-titanium dioxide was dispersed in anhydrous ethanol and stirred for 10-15 min, then ultrasonically dispersed at 20-23℃ for 25-30 min to obtain a nano-titanium dioxide mixture. Stearic acid was added to the nano-titanium dioxide mixture and stirred for 10-15 min, then ultrasonically dispersed at 35-40℃ for 25-30 min. The temperature was then raised to 65-70℃ and magnetically stirred for 1.5-2 h. After centrifugation for 3-5 min, the resulting solution was allowed to stand at 20-25℃ for 11-13 h. The supernatant was discarded, and the lower solid-liquid mixture was dried at 75-85℃ for 1-1.5 h and ground to obtain stearic acid-modified nano-titanium dioxide.

7. The method for preparing a yellowing-resistant transparent asphalt material according to claim 6, characterized in that: The mass ratio of the nano-titanium dioxide, anhydrous ethanol, and stearic acid is 1:20:0.

2.

8. The method for preparing a yellowing-resistant transparent asphalt material according to claim 1, characterized in that: In step 2, the heating shearing temperature is 145~155℃, the shearing speed is 5000~5500 r / min, and the shearing time is 1~2 h; the shearing development shearing speed is 5000~5500 r / min, the shearing time is 50~60 min, the development temperature is 160~165℃, and the development time is 2~3 h.

9. The method for preparing a yellowing-resistant transparent asphalt material according to claim 1, characterized in that: In step 3, the constant temperature is 160~165℃, the shearing speed is 5000~5500r / min, the shearing time is 45~55min, the heat preservation temperature is 160~170℃, and the heat preservation time is 40~50min.

10. A transparent asphalt material resistant to yellowing, characterized in that: Prepared by the method according to any one of claims 1-9.